Assessing Impact of Health Education in Improving Knowledge of Children on Child Sexual Abuse - Bansal, Prerna; Shrestha, Ayasha; Upadhyay, Hari Prasad; Khadka, Kamal; Koirala, Pallavi (Journal of Nepal Health Research Council, 2023)
Background: Every year, millions of children around the world face sexual abuse and exploitation. Sexual and reproductive health education is an important form of health promotion action against it. This study aims to assess the impact of health education program in improving knowledge of the children on child sexual abuse. Methods: A school based pre-experimental study was done among 120 lower secondary level students of a private school in Bharatpur municipality of Chitwan District, Nepal during March 2021. An interventional health education program imparting knowledge on child sexual abuse and its preventive measures was given to the children. Their knowledge was assessed and compared before and after intervention using paired t-test. Data analysis was done using SPSS version 17 software. Results: The mean age of children was 13.77±0.65 years with 1:1.18 girls to boys ratio. The level of knowledge of the children on child sexual abuse and its preventive measures increased significantly post-intervention as compared to pre-intervention. The mean scores of post-test (29.80±4.53) was higher than pre-test (17.04±6.96). The intervention was proved effective with statistically significant t-test values (t=20.996, p=<0.001). About 6.7% children disclosed an experience of child abuse post-intervention. Conclusions: The school based health education program effectively increased the knowledge of the children on child sexual abuse, thus helping in preventing and protecting them from child sexual abuse and its harmful effects. Keywords: Child abuse; health education; school health services; sexual, touch.